EKSPERIMENTASI MODEL PEMBELAJARAN KOOPERATIF TIPE TEAM ASSISTED INDIVIDUALIZATION (TAI) DAN NUMBERED HEADS TOGETHER (NHT) DENGAN PENDEKATAN SAINTIFIK PADA MATERI BILANGAN DITINJAU DARI KEMANDIRIAN BELAJAR SISWA SMP NEGERI KELAS VII DI-KABUPATEN BOYOLALI - Pratama, Fika Widya; Kusmayadi, Tri Atmojo; Riyadi, Riyadi (Jurnal Pembelajaran Matematika, 2016)
Abstract: The aim of the research was to determine the effect of learning models on mathematics learning achievement viewed from self regulated learning (SRL). The learning models compared were cooperative learning model of TAI-PS, NHT-PS, and classical-PS learning. The research used the quasi-experimental research with the factorial design of 3 Â 3. The population of the research were all of the students in grade VII of junior high school at Boyolali regency in the first semester of the academic year 2014/2015. The hypotheses of the research were analyzed by using two-way analysis of variance with unbalanced cells at the significance level of . The result of these research are as follows. (1) TAI-PS model gives better mathematics learning achievement than NHT-PS and classical-PS, whereas NHT-PS model gives better mathematics learning achievement than classical-PS. (2) Students with high SRL are better in mathematics learning achievement than students with medium and low SRL, and also medium SRL have better mathematics learning achievement than low SRL. (3) (a) TAI-PS with high, medium, and low SRL have the same mathematics learning achievement. (b) NHT-PS with high and medium SRL and also medium and low SRL have the same mathematics learning achievement, whereas high SRL have better mathematics learning achievement than students with low SRL. (c) classical-PS with high SRL are better in mathematics learning achievement than students with medium and low SRL, whereas students with medium and low SRL have the same mathematics learning achievement. (4) (a) The high SRL with the TAI-PS, NHT-PS, and classical-PS give the same mathematics learning achievement. (b) The medium SRL with TAI-PS and NHT-PS, and also NHT-PS and classical-PS give the same mathematics learning achievement, whereas TAI-PS give better in mathematics learning achievement than classical-PS. (c) The low SRL with TAI-PS and NHT-PS give the same mathematics learning achievement, whereas TAI-PS and NHT-PS give better in mathematics learning achievement than classical-PS.Keywords: Team Assisted Individualization (TAI), Numbered Heads Together (NHT), classical learning, scientific approach, and Self-Regulated Learning (SRL).